Changes in Gene Expression of the MCU Complex Are Induced by Electrical Stimulation in Adult Skeletal Muscle - Quezada, Esteban R.; Díaz-Vegas, Alexis; Jaimovich, Enrique; Casas, Mariana (Frontiers in Physiology, 2021)
The slow calcium transient triggered by low-frequency electrical stimulation (ES) in adult muscle fibers and regulated by the extracellular ATP/IP3/IP3R pathway has been related to muscle plasticity. A regulation of muscular tropism associated with the MCU has also been described. However, the role of transient cytosolic calcium signals and signaling pathways related to muscle plasticity over the regulation of gene expression of the MCU complex (MCU, MICU1, MICU2, and EMRE) in adult skeletal muscle is completely unknown. In the present work, we show that 270, 0.3 ms-long pulses at 20 Hz ES (and not at 90 Hz) transiently decreased the mRNA levels of the MCU complex in mice flexor digitorum brevis isolated muscle fibers. Importantly, when ATP released after 20 Hz ES is hydrolyzed by the enzyme apyrase, the repressor effect of 20 Hz on mRNA levels of the MCU complex is lost. Accordingly, the exposure of muscle fibers to 30 µM exogenous ATP produces the same effect than 20 Hz ES. Moreover, the use of apyrase in resting conditions (without ES) increased mRNA levels of MCU, pointing the importance of extracellular ATP concentration over MCU mRNA levels. The use of xestospongin B (inhibitor of IP3 receptors) also prevented the decrease of mRNA levels of MCU, MICU1, MICU2, and EMRE mediated by a low-frequency ES. Our results show that the MCU complex can be regulated by electrical stimuli in a frequency-dependent manner. The changes observed in mRNA levels may be related to changes in the mitochondria, associated with the phenotypic transition from a fast to a slow type muscle, according to the described effect of this stimulation frequency on muscle phenotype. The decrease in mRNA levels of the MCU complex by exogenous ATP and the increase in MCU levels when basal ATP is reduced with the enzyme apyrase, indicates that extracellular ATP may be a regulator of the MCU complex. Moreover, our results suggest that this regulation is part of the axes linking low-frequency stimulation with ATP/IP3/IP3R.